2016
DOI: 10.1038/ncomms11581
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic cyclin D1 regulates cell invasion and metastasis through the phosphorylation of paxillin

Abstract: Cyclin D1 (Ccnd1) together with its binding partner Cdk4 act as a transcriptional regulator to control cell proliferation and migration, and abnormal Ccnd1·Cdk4 expression promotes tumour growth and metastasis. While different nuclear Ccnd1·Cdk4 targets participating in cell proliferation and tissue development have been identified, little is known about how Ccnd1·Cdk4 controls cell adherence and invasion. Here, we show that the focal adhesion component paxillin is a cytoplasmic substrate of Ccnd1·Cdk4. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
111
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(124 citation statements)
references
References 51 publications
9
111
0
1
Order By: Relevance
“…As mentioned above, Ccnd1 induces invasion through the phosphorylation of paxillin in the cell membrane. 5 In agreement with this, we have observed that a phosphomimetic allele of paxillin rescues the metastatic potential of Ccnd1-deficient cells without affecting their proliferative state. This also agrees with the reported requirement for phospho-Pxn for the induction of metastases in different tumor models.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…As mentioned above, Ccnd1 induces invasion through the phosphorylation of paxillin in the cell membrane. 5 In agreement with this, we have observed that a phosphomimetic allele of paxillin rescues the metastatic potential of Ccnd1-deficient cells without affecting their proliferative state. This also agrees with the reported requirement for phospho-Pxn for the induction of metastases in different tumor models.…”
supporting
confidence: 73%
“…For instance, Ccnd1 has been shown to interact with filamin A (FLNA) and to co-localize with this protein in membrane ruffles. 8 Our recent contribution confirms that a subpopulation of the Ccnd1 protein is localized in the membrane, 5 together with paxillin and active Rac1, and strongly suggests that this localization is functionally relevant in the regulation of cell adhesion and invasion. Hence, we provide new and compelling evidence that cytoplasmic Ccnd1 has an important role in regulating different pathways to induce migration and invasion.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…Recent studies have demonstrated that cyclinD1 has been associated with tumor invasion and metastasis in clinical studies and in vivo experiments, and cyclin D1 regulates invasion and metastasis through the phosphorylation of paxillin. [24][25][26] In addition to the suppression of cell growth by SOX6 in the ovarian cancer cells, inhibitory effect of SOX6 on ovarian cancer cell invasion was also observed in this study, suggesting that SOX6 may prevent metastasis of ovarian tumors. The SOX family of transcription factors has emerged as modulators of canonical Wnt/β-catenin signaling in diverse development and disease contexts.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, cyclin D1 was highly immune reactive in the cytoplasm of Bmpr2 fl/+ MPCs and in the nuclei of βOE MPCs. Cytoplasmic cyclin D1 can regulate invasion as well as survival (37), while nuclear localization is typically associated with proliferation and survival (38).…”
Section: Resultsmentioning
confidence: 99%